FORMULASI KOMPETENSI INTI GREEN NITROGEN DALAM LAYANAN NITROGEN DI SPBU PERTAMINA - Freddy Simbolon; Retno Dewanti; Ina Melati (Bina Nusantara University, 2013)
Green Nitrogen is a pioneerand the largest in the nitrogen charging service and tire for motor vehicles in Pertamina gas station. At the young age of three years the company has not even been able to developthe market from Medan to Denpasar. Along with the development of the service market nitrogen and tubeless tire, the newer companies that have sprung up in order to create competition in the market. As a result of the emergence of competition, the need for companies to build core competencies in order to retain customers and a market leader. This study aims to formulate the company's core competencies in order to become the market leader in the service of nitrogen and tubeless tire. The method of research using qualitative methods of data collection through the Focus Group Discussion (FGD). Based on the result showed that the core competencies that must be owned by company in strengthening the company's competitive position in the industry nitrogen and tire services in Pertamina gas station is to build expertise in the development of products, services and the latest business that exceeds customer expectations.